Exercise and Use of Enhancement Drugs at the Time of the COVID-19 Pandemic: A Multicultural Study on Coping Strategies During Self-Isolation and Related Risks - Dores, Artemisa R.; Carvalho, Irene P.; Burkauskas, Julius; Simonato, Pierluigi; De Luca, Ilaria; Mooney, Roisin; Ioannidis, Konstantinos; Gómez-Martínez, M. Ángeles; Demetrovics, Zsolt; Ábel, Krisztina Edina; Szabo, Attila; Fujiwara, Hironobu; et al. (Frontiers in Psychiatry, 2021)
Introduction: Little is known about the impact of restrictive measures during the Covid-19 pandemic on self-image and engagement in exercise and other coping strategies alongside the use of Image and Performance-Enhancing Drugs (IPEDs) to boost performance and appearance. Objectives: To assess the role of anxiety about appearance and self-compassion on the practice of physical exercise and use of IPEDs during lockdown. Methods: An international online questionnaire was carried out using the Exercise Addiction Inventory (EAI), the Appearance Anxiety Inventory (AAI), and the Self-Compassion Scale (SCS) in addition to questions on the use of IPEDs. Results: The sample consisted of 3,161 (65% female) adults from Italy (41.1%), Spain (15.7%), the United Kingdom (UK) (12.0%), Lithuania (11.6%), Portugal (10.5%), Japan (5.5%), and Hungary (3.5%). The mean age was 35.05 (SD = 12.10). Overall, 4.3% of the participants were found to engage in excessive or problematic exercise with peaks registered in the UK (11.0%) and Spain (5.4%). The sample reported the use of a wide range of drugs and medicines to boost image and performance (20%) and maintained the use during the lockdown, mostly in Hungary (53.2%), Japan (41.3%) and the UK (32.0%), with 6.4% who started to use a new drug. Significant appearance anxiety levels were found across the sample with 18.1% in Italy, 16.9% in Japan and 16.7% in Portugal). Logistic regression models revealed a strong association between physical exercise and IPEDs use. Anxiety about appearance also significantly increased the probability of using IPEDs. However, self-compassion did not significantly predict such behaviour. Anxiety about appearance and self-compassion were non-significant predictors associated with engaging in physical exercise. Discussion and conclusion: This study identified risks of problematic exercising and appearance anxiety amongst the general population during the COVID-19 lockdown period across all the participating countries. Such behaviours were positively associated with the unsupervised use of IPEDs, although no interaction between physical exercise and anxiety was observed. Further considerations are needed to explore the possible impact of socially restrictive measures among vulnerable groups, namely males, and the implementation of more targeted responses.